The impact of pandemic covid-19 crisis toward contractor during construction stage in Perak - Anuar, Ahmad Haziq Rifqi (2023)
On March 18, 2020, the Movement Control Order (MCO) will go into force. The MCO has had an effect on the Malaysian construction industry. When employment is at risk due to covid-19, a variety of industries "work from home." In the current COVID-19 environment, however, construction projects must manage job sites. Due to the halt of activity on construction sites during the pre- and post-lockdown, the contractor is the party most adversely affected by the Covid-19 pandemic problem. The purpose of this study is to determine the influence of the covid 19 pandemic crisis on the progress of construction projects from the contractor's perspective. By identifying the issues and determining the effects of Covid-19 on the progress of construction project work, this research proposes appropriate actions to be implemented by construction stakeholders to tackle the challenges faced by contractors during the construction phase. This study was conducted quantitatively by a questionnaire survey. Random sampling was used to deliver 101 questionnaires to grade G1 through G3 contractors in Perak, of which 104 were returned.